Associating Fitness Position and Way of life in College Students - Sedai, Shyam Prasad (Journal of Balkumari College, 2019)
The study aimed to compare health status and lifestyle i n university students. The participants were college students from health and physical Ed. majors (N = 195, Mean = 20.9, SD = 1.87) and population Ed. majors (N = 195, Mean = 2 1.73, SD = 0.93) in Chitwan. The Diagnostic Inventory of Health and Life habit (DIHAL.2) scale (Tokunaga, 2003) was administered to all participants. A one-way sample t-test was used to analyze the difference in both interdepartmental and gender effects. Results of t-test indicated that there were significantly difference in physical health, social health and life habit. Moreover, students majoring in health and physical education were scored lower on the mental health domain compared to the physical and social health domains. The practical implication of this study focused on finding the difference between the students who regularly exercised and those who did not, and considered the characteristics of gender.